Pultrusion of fibre reinforced thermoplastic pre-impregnated materials. (15th March 2016) - Novo, P.J.; Silva, J.F.; Nunes, J.P.; Marques, A.T.
Abstract: Fibre reinforced thermoplastic pre-impregnated materials produced continuously by diverse methods and processing conditions were used to produce composites using pultrusion. The processing windows used to produce these materials and composites profiles were optimized by using the Taguchi/DOE (Design of Experiments) methods. Those composites were then submitted to mechanical testing and microscopy analysis. The obtained results were compared with the expected theoretical ones predicted from the Rule Of Mixtures (ROM) and with those of similar engineering conventional available materials. The results obtained shown that produced composites have adequate properties for applications in common and structural engineering markets.